Vascular endothelial cells evade complement‐mediated membrane injury via Weibel‐Palade body mobilization. (4th June 2020) - Riedl Khursigara, Magdalena; Schlam, Daniel; Noone, Damien G.; Bruno, Valentina; Ortiz-Sandoval, Carolina G.; Pluthero, Fred G.; Kahr, Walter H. A.; Bowman, Mackenzie L.; James, Paula; Grinstein, Sergio; Licht, Christoph
Abstract: Background: Defective complement inhibition can lead to the formation of membrane attack complexes (MAC; C5b‐9) on the plasma membranes of vascular endothelial cells, resulting in injury that drives the progression of thrombotic microangiopathy (TMA), a key pathology in kidney disease. Objective/Methods: We examined the response of human endothelial cells to complement‐mediated damage using blood outgrowth endothelial cells (BOECs) derived from healthy donors. BOECs were sensitized to complement factors present in normal human serum to induce the formation of C5b‐9 on their plasma membranes. Results: This triggered an expected abrupt rise in intracellular Ca 2+ reflecting membrane leakage. Remarkably, while intracellular Ca 2+ remained elevated, membrane leakage ceased within 30 minutes, and cells did not show significant death. Extensive mobilization of Weibel‐Palade bodies (WPBs) was observed along with secretion of von Willebrand factor (VWF). The potential role of WPBs and VWF in mitigating complement‐mediated damage was examined by comparing the effects of C5b‐9 on BOECs derived from von Willebrand disease (VWD) patients expressing reduced amounts of VWF, lacking expression of functional VWF, or lacking both VWF and WPBs. BOECs lacking WPBs were not resistant to complement‐mediated damage, but became resistant when transfected to express VWF (and thus WPBs). Conclusion: We conclude that BOECs exposed to C5b‐9 attack respond by mobilizing WPBs, which mitigate and repair damage by fusing with the plasma membrane. We propose that a similar cell‐specific response may protect the vascular endothelium from complement‐mediated damage in vivo .